Lifestyle potential against recurrent intraoral herpes recurrence rate: a case series: Potensi gaya hidup terhadap tingkat kekambuhan recurrent intraoral herpes: serial kasus - Ani Megawati; Wahyu Hidayat (Makassar Dental Journal PDGI Makassar, 2022)
Introduction: Herpes Simplex Virus type 1 (HSV-1) is the virus that most often infects the oral cavity. HSV-1 in the latent phase migrates to the trigeminal ganglion after primary infection and can reactivate to cause recurrent intraoral herpes (RIH). The recurrence of RIH is multifactorial and triggered by decreased immunity, fatigue, hypersensitivity, stress, and ultraviolet. Case: Three male patients came to the Oral Disease Clinic with ulcers in the oral cavity. The patients experienced prodromal symptoms and the characteristic features of RIH were multiple rounded ulcers spreading and surrounded by erythematous areas. Anti-HSV-1 IgG examination showed reactive results. Management: The therapy was acyclovir and trigger factor modifica-tion. The oral lesions of all patients recovered after therapy and there were no new lesions. Conclusion: Lifestyle and habits have a high potential to be a triggering factor for RIH recurrence, so comprehensive treatment is needed to prevent recurrence.